Szilágyi Erzsébet és az egyház - Csifó Tamás (2019)
Elisabeth Szilágyi of Horogszeg is usually referred to as only the widow of John Hunyadi, the famous warlord and governor of the Kingdom of Hungary, and the mother of King Matthias I, one of the greatest monarchs in the late medieval history of Hungary. Her role in the liberation of her son, and then helping him ascending the throne of the Kingdom is considered to be the most well-known deeds of her. However, researching her life highlights the fact, that the story of the 15th century dowager is remarkable from other perspectives too. Among other things, these include her relations with the Catholic Church, her church policy and in connection with these, her religious beliefs. This subject is a relatively less processed and even less emphasized chapter of Elizabeth's story. Therefore, in this study, I would like to give a glimpse of the system of Elisabeth Szilágyi's ecclesiastical liaisons. In my analysis, I discuss Elisabeth's personal relations with the Hungarian high priests, her contacts with chapters, her papal acquaintance, her attitude to the monastic church, and our knowledge of her religious life.